Analisis Berthing Time terhadap Kinerja Pelayanan Bongkar Muat Curah Kering - Wiranata, Alfan Dwi Wahyu; Sudirman, Sudirman; Agus Setiono, Beni (Universitas Hang Tuah, 2021)
The research location at PT. Berlian Manyar Sejahtera as the Operator of the JIIPE Manyar Gresik by using the independent variable Berthing Time (the first time the ship starts tying the rope to untie the rope at the mooring) with the dependent variable is the loading and unloading service performance. The population in this study were employees of the operational division at the Port of JIIPE (Java Integrated Industrial Port Estate) PT. Manyar Prosperous Diamonds. While the samples (informants) used by this researcher are ship foremen and checkers. The results showed that the average working time of ships at moorings (ET:BT) was 53.19%, still below the standard specified in the Decree of the Director General of Sea Transportation Number: UM.002/38/18/DJPL-2011, which is 70 %, in fact, none of them reached 90% of the specified standard, while the average time for loading and unloading service productivity performance (T/G/J) reached 153.23 T/G/J, above the standard specified in the Decree of the Director General Sea Transportation No.: UM.002/38/18/DJPL-2011 which is 125 T/G/J although there are some activities that are still below standard. From the results of observations and interviews with the company, it can be concluded that the main factor causing the non-achievement of the berthing time performance standard above is the level of Effective Time caused by the high level of Idle Time and Not Operation Time. For performance standards of loading and unloading service productivity (T/G/J), the cause of not achieving performance standards is due to loading and unloading support factors.